MSH homeobox 1 polymorphisms and the risk of non‐syndromic orofacial clefts: a meta‐analysis. (17th April 2018) - Gu, Min; Zhang, Yan; Liu, Hualian; Liu, Jue; Zhu, Danxia; Yang, Xu
Abstract : MSH homebox 1 ( MSX1 ) is a susceptibility gene for non‐syndromic orofacial clefts (NSOCs). Here, a meta‐analysis was conducted to assess their associations. A systematic search of PubMed to 1 September 2017, was performed to retrieve all eligible studies. Odds ratios (ORs) were used to calculate the associations. The stability of the results was evaluated by sensitivity analysis. Publication bias was assessed using Begg's funnel plots and the Egger test. In silico Msx1 expression during early mouse craniofacial development was evaluated by the Gene Expression Omnibus. In the overall analysis, MSX1 rs12532 (G>A) contributed to a decreased risk of NSOC. In an analysis stratified according to disease type, rs12532 was associated with the risk of cleft palate only (CPO) but not with the risk of cleft lip with or without cleft palate (CL/P). The association of rs12532 with the occurrence of NSOC in Asian and Caucasian populations but not South American populations was observed in an analysis stratified according to ethnicity. However, no significant associations were detected between any of the other MSX1 SNPs and the risk of NSOC in either the overall or subgroup analysis. The Msx1 gene was widely expressed in mouse craniofacial structures from embryonic day (E)8.5‐E10.5. Taken together, the study indicates that MSX1 rs12532 is associated with the risk of NSOC.